Perancangan Interior Eco Hotel di Sendang Biru, Malang - Aditama, Felicia Rezki (Intra, 2014)
Interior Design of Eco Hotel in Sendang Biru, Malang is aim to provide lodging facilities in the tourist area of Sendang Biru that give insight and inspiration to the community about the implementation of eco-interior as well as the growing concern for nature. Application of eco-interior aspect of the approach is done through 8 are visible on the facilities that are designed, the lobby, restaurant, outdoor cafÃ©, gym, spa, bread shop, library, workshops, and hotel rooms. Workshop facility, allowing communities to better understand and recognize eco-interior as well as its application, through information and training related to creativity eco-interior, and invite the community to care for the natural environment is currently experiencing issues, namely global warming. Therefore, designers design a lodging facility that can inspire the public about the application of eco-interior through the application of the building as a hotel and workshop facilities where visitors can better understand the eco-interior with teaching and channeling creativity.